Caffeic acid phenethyl ester restores mitochondrial homeostasis against peritoneal fibrosis induced by peritoneal dialysis through the AMPK/SIRT1 pathway - Ying Lu; Luyan Gao; Wenwen Zhang; Ying Zeng; Ji Hu; Kai Song (Renal Failure)
Increasing evidence suggests that peritoneal fibrosis induced by peritoneal dialysis (PD) is linked to oxidative stress. However, there are currently no effective interventions for peritoneal fibrosis. In the present study, we explored whether adding caffeic acid phenethyl ester (CAPE) to peritoneal dialysis fluid (PDF) improved peritoneal fibrosis caused by PD and explored the molecular mechanism. We established a peritoneal fibrosis model in Sprague–Dawley rats through intraperitoneal injection of PDF and lipopolysaccharide (LPS). Rats in the PD group showed increased peritoneal thickness, submesothelial collagen deposition, and the expression of TGFβ1 and α-SMA. Adding CAPE to PDF significantly inhibited PD-induced submesothelial thickening, reduced TGFβ1 and α-SMA expression, alleviated peritoneal fibrosis, and improved the peritoneal ultrafiltration function. In vitro, peritoneal mesothelial cells (PMCs) treated with PDF showed inhibition of the AMPK/SIRT1 pathway, mitochondrial membrane potential depolarization, overproduction of mitochondrial reactive oxygen species (ROS), decreased ATP synthesis, and induction of mesothelial-mesenchymal transition (MMT). CAPE activated the AMPK/SIRT1 pathway, thereby inhibiting mitochondrial membrane potential depolarization, reducing mitochondrial ROS generation, and maintaining ATP synthesis. However, the beneficial effects of CAPE were counteracted by an AMPK inhibitor and siSIRT1. Our results suggest that CAPE maintains mitochondrial homeostasis by upregulating the AMPK/SIRT1 pathway, which alleviates oxidative stress and MMT, thereby mitigating the damage to the peritoneal structure and function caused by PD. These findings suggest that adding CAPE to PDF may prevent and treat peritoneal fibrosis.